2023
DOI: 10.1002/joa3.12838
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial appendage occlusion after thromboembolic events or left atrial appendage sludge during anticoagulation therapy: Is two better than one? Real‐world experience from a tertiary care hospital

Abstract: Background:The role of left atrial appendage occlusion (LAAO) for atrial fibrillation patients that during oral anticoagulant therapy (OAC) suffer from ischemic events or present LAA sludge, and the best postinterventional anticoagulant regimen, need to be defined. We present our experience with a hybrid approach of LAAO+ lifelong OAC therapy in this cohort of patients.Methods: Out of 425 patients treated with LAAO, 102 underwent LAAO because, despite OAC, suffered from ischemic events or presented with LAA sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
0
8
2
Order By: Relevance
“…Recently, a beneficial synergistic effect of continuing OAC plus LAA occlusion in high-risk patients without contraindications for anticoagulation in reducing systemic and cerebral embolic events, as well as allcause mortality, has been proposed (4, 24, 51, 52). In our series, the presence of DRT was not detected during follow-up; its incidence has been reported to be 1.5 -14% (20,24,53,54). Margonatto et al (24), reported 13% of DRT in their patients, occurred in those who had been discharged under dual antiplatelet therapy, and it resolved when switching to OAC.…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…Recently, a beneficial synergistic effect of continuing OAC plus LAA occlusion in high-risk patients without contraindications for anticoagulation in reducing systemic and cerebral embolic events, as well as allcause mortality, has been proposed (4, 24, 51, 52). In our series, the presence of DRT was not detected during follow-up; its incidence has been reported to be 1.5 -14% (20,24,53,54). Margonatto et al (24), reported 13% of DRT in their patients, occurred in those who had been discharged under dual antiplatelet therapy, and it resolved when switching to OAC.…”
Section: Discussioncontrasting
confidence: 44%
“…In our series, the presence of DRT was not detected during follow-up; its incidence has been reported to be 1.5 -14% (20,24,53,54). Margonatto et al (24), reported 13% of DRT in their patients, occurred in those who had been discharged under dual antiplatelet therapy, and it resolved when switching to OAC.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…A call for therapeutic alternatives in patients with "valvular AF" and OAC failure LAAC in patients with AF and failure of OAC therapy is a continually expanding indication due to proved safety and efficacy of the procedure and no need for antithrombotic therapy enhancement [18,19]. However, all LAAC devices that have acquired commercial approvement so far were tested only in the specific population affected by non valvular AF and anticoagulant contraindication.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, some retrospective studies [ 24 ] and one multicenter registry [ 76 ] highlighted the feasibility and safety of this procedure using Amulet (St. Jude Medical) and Watchman (Boston Scientific) devices. In a study, LAAC was proposed in combination with OAC as an enhancement of antithrombotic therapy in AF patients incurred in stroke/systemic embolism despite OAC, reporting optimistic results in terms of feasibility and safety after 5 years of follow-up [ 77 ]. The use of CPD in this scenario may further reduce the risk of severe intraprocedural complications.…”
Section: Cerebral Protection In Ep Labsmentioning
confidence: 99%